2015
DOI: 10.5750/ejpch.v3i4.1019
|View full text |Cite
|
Sign up to set email alerts
|

A survey of women’s birth experiences in Scotland using the Birth Satisfaction Scale (BSS)

Abstract: Background: 'Birth satisfaction' is important since experience of labour can influence women's post-natal adjustment. Objective: To explore: (1) childbearing women's experiences of 'birth satisfaction' and (2) identify contexts in which it is more appropriate to use the 30-item Birth Satisfaction Scale (BSS) or the 10-item BSS-Revised (BSS-R). Study design: A quantitative survey was conducted using the 30-item BSS. As a function of completing the 30-item BSS, participants also completed the short-form 10-item … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
1
3
0
3
Order By: Relevance
“…It was found that there were statistically significant differences between these two groups in terms of satisfaction with childbirth only in evaluating the level of anxiousness (those who gave birth vaginally were less anxious). The study conducted on birthing mothers in Scotland (also with the BSS-R questionnaire) showed that women who had a spontaneous vaginal birth were a lot more satisfied with childbirth as those who gave birth with a caesarean section (Hollins Martin & Martin, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It was found that there were statistically significant differences between these two groups in terms of satisfaction with childbirth only in evaluating the level of anxiousness (those who gave birth vaginally were less anxious). The study conducted on birthing mothers in Scotland (also with the BSS-R questionnaire) showed that women who had a spontaneous vaginal birth were a lot more satisfied with childbirth as those who gave birth with a caesarean section (Hollins Martin & Martin, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The first set that included 12 open and closed type questions referred to social and demographic data on childbirth. The second section included the Birth Satisfaction Scale -Revised (BSS-R) questionnaire, in Slovenian 'Lestvica zadovoljstva s porodom 2', that has been verified (Cronbach coefficient alfa was 0.79 in the original version) and used in some similar studies (Hollins Martin, 2014;Hollins Martin & Martin, 2015). The BSS-R questionnaire is composed of 10 questions, whereby 1 is the lowest and 5 is the highest level of agreement.…”
Section: Description Of the Research Instrumentmentioning
confidence: 99%
See 3 more Smart Citations